Copper(II) complexes of bis(aryl-imino)acenaphthene ligands: synthesis, structure, DFT studies and evaluation in reverse ATRP of styrene - Fliedel, Christophe (2014)
Two new Ar-BIAN Cu(II) complexes (where Ar-BIAN = bis(aryl-imino)acenaphthene) of formulations [CuCl2(Mes-BIAN)] (1) (Mes = 2,4,6-Me3C6H2) and [CuCl2(Dipp-BIAN)] (2) (Dipp = 2,6-iPr2C6H3) were synthesised by direct reaction of CuCl2 suspended in dichloromethane with the respective ligands Mes-BIAN (L1) and Dipp-BIAN (L2), dissolved in dichloromethane, under an argon atmosphere. Attempts to obtain these compounds by solubilising CuCl2 in methanol and adding a dichloromethane solution of the corresponding ligand, under aerobic conditions, gave also compound 1, but, in the case of L2, the Cu(I) dimer [CuCl(Dipp-BIAN)]2 (3) was obtained instead of compound 2. The compounds were fully characterised by elemental analyses, MALDI-TOF mass spectrometry, FT-IR, 1H NMR and EPR spectroscopic techniques. The solid-state molecular structures of compounds 1?3 were determined by single crystal X-ray diffraction, showing the expected chelation of the Ar-BIAN ligands and two chloride ligands completing the coordination sphere of the Cu(II) centre. In the case of the complex 1, an intermediate coordination geometry around the Cu(II) centre, between square planar and tetrahedral, was revealed, while the complex 2 showed an almost square planar geometry. The structural differences and evaluation of energetic changes were rationalised by DFT calculations. Analysis of the electrochemical behaviour of complexes 1?3 was performed by cyclic voltammetry and the experimental redox potentials for Cu(II)/Cu(I) pairs have been compared with theoretical values calculated by DFT in the gas phase and in dichloromethane and methanol solutions. The complex 1 exhibited good activity in the reverse atom transfer radical polymerisation (ATRP) of styrene.